2010
DOI: 10.1534/genetics.110.120337
|View full text |Cite
|
Sign up to set email alerts
|

The Rapidly Evolving Centromere-Specific Histone Has Stringent Functional Requirements inArabidopsis thaliana

Abstract: Centromeres control chromosome inheritance in eukaryotes, yet their DNA structure and primary sequence are hypervariable. Most animals and plants have megabases of tandem repeats at their centromeres, unlike yeast with unique centromere sequences. Centromere function requires the centromere-specific histone CENH3 (CENP-A in human), which replaces histone H3 in centromeric nucleosomes. CENH3 evolves rapidly, particularly in its N-terminal tail domain. A portion of the CENH3 histone-fold domain, the CENP-A targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 45 publications
4
120
1
Order By: Relevance
“…Similarly, the CENH3 protein from A. thaliana can be detected in the centromeres of all chromosomes of allotetraploid A. thaliana × Arabidopsis arenosa hybrid A. suecica (21). Our observation based on sexually generated hybrids supports previous cross-species CENH3 incorporation experiments in transgenic organisms (27,51,(60)(61)(62), for which it was reported that CENH3s of closely related species can target centromeres in alien species.…”
Section: Cenh3 Behavior In Stable Speciessupporting
confidence: 88%
“…Similarly, the CENH3 protein from A. thaliana can be detected in the centromeres of all chromosomes of allotetraploid A. thaliana × Arabidopsis arenosa hybrid A. suecica (21). Our observation based on sexually generated hybrids supports previous cross-species CENH3 incorporation experiments in transgenic organisms (27,51,(60)(61)(62), for which it was reported that CENH3s of closely related species can target centromeres in alien species.…”
Section: Cenh3 Behavior In Stable Speciessupporting
confidence: 88%
“…Among our collection of variant CENH3 strains 16,22,23 , the previously described GFP-tailswap strain 16 is the optimal HI based on its haploid induction efficiency and ease of use (see Methods, Fig. 1a, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, a tetraploid TILLING plant carrying the desired mutant allele must be converted to diploid for easy genetic analysis. In fact, the cenh3-1 allele used to create the HI strain was originally isolated from a tetraploid TILLING population that conventionally required two transitional generations via a triploid bridge to generate a diploid CENH3/ cenh3-1 heterozygote 22,33,34 . With a HI strategy, we hypothesized that a tetraploid TILLING population can be converted to diploid by a single cross.…”
Section: Resultsmentioning
confidence: 99%
“…It was revealed that the core domain for centromere targeting was involved in the C terminal histone fold domain, and the detailed amino acid sequences corresponding to the function were different among them [2731]. In plants, similar work had been carried out in the model dicot plant A. thaliana [32]. By using a cenh3 null mutant, the endogenous CENH3 could be completely replaced by transgenic protein variants [33].…”
Section: Centromeric Histone H3 Variant Cenh3mentioning
confidence: 99%
“…By using a cenh3 null mutant, the endogenous CENH3 could be completely replaced by transgenic protein variants [33]. Through substituting the CENH3 N terminal domain or C terminal domain with the histone H3.3, the results showed that either the H3 N terminal tail or the CENH3 N terminal tail combined with the CENH3 C terminal were sufficient for mitosis, while inserting the CATD domain of CENH3 into the H3 could not complement the function of CENH3 [32]. One transgenic protein variant referred to as GFP-tailswap, in which the CENH3 N terminal domain was substituted by the H3.3 N terminal domain with a GFP fluorescent protein in front of the fusion protein, could rescue the lethal phenotype of the cenh3 null mutant but was highly sterile.…”
Section: Centromeric Histone H3 Variant Cenh3mentioning
confidence: 99%